PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL ACTIVITY OF ATLANTIA MONOPHYLLA (AM) EXTRACT - HARITHA, MANCHI; KUDAGI, BL; MOHAN, PATHAPATI RAMA; CHANDRA, VURIMI BHOPAL; KAMAL, SK SALMA; MANCHI, RAJESH KUMAR; NELAVALA, ANJANI DEVI (International Journal of Current Pharmaceutical Research, 2024)
Objective: Plants have long been recognised for their wide range of biological properties, including antibacterial, analgesic, anticancer, antipyretic, and antihypertensive action. They are also a significant source of several chemicals with biological activity. The Rutaceae family consists of a small shrub Atlantia monophylla. It is available all over India. The leaves were employed as an insect repellent and to alleviate swellings. The root bark has been found to contain atalaphyllinine, atalantin, dehydroatalantin, cycloepiatalantin, and atalaphylline 3, 5-dimethyl ether. Essential oil extracted from the leaves was reported to have antimicrobial properties. Methods: To evaluate the phytochemicals Standard chemical methods for each o the compounds were used – like Tannins (0.1% ferric chloride), saponins (2 ml of water)/flavonoids (with NaOH), Alkaloids (Drangandooff reagent), protein (Million’s reagent) steroids (10% sulphuric acid), anthraquinones (aqueous ammonia), Phenols (lead acetate), terpenoids, (3% sulphuric acids) Carbohydrates (Benedict’s reagent). Disc plate method was used to evaluate the antimicrobial activity of the extract Results: The results of this study identified the presence of tannins, flavonoids, alkaloids, proteins, steroids, phenols, terpenoids, and carbohydrates in the AM extract. The microbiological studies revealed better inhibitions of microbes compared to standard drugs. Conclusion: Tannins, flavonoids, proteins, steroids, phenols, terpenoids, carbohydrates and alkaloids were extracted from the AM extract. The extract has significant microbiological action.